Induction of Estrus in Postpartum Anestrus Crossbred Cattle - Niaz, Sumiya; Naiko, Mehrajuddin; Islam, Rafiqul; Lone, Farooz Ahmad; Khan, Azmat Alam (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present experiment was designed for estrus induction in post-partum anestrus cattle. A total of 120 cows were examined for reproductive status, and 30 were incorporated in induction, including 24 anestrus and 6 normal cyclic cows. The cows were assigned to 5 groups (6 animals per group). The group-1 cows were induced using Ovsynch protocol, while group-2 cows were inserted TRIU-B (958 mg progesterone) intra-vaginal and were inseminated at a fixed time. The group-3 cows were supplemented with a standard chelated mineral mixture of 40 g per-oral daily for 45 days and were inseminated on observed estrus. Group-4 included normal cyclic untreated cows inseminated at estrus. The group-5 included untreated anestrus control cows. Estrus induction response was 100% in groups 1 and 2, 66.66%, and 0.00% in groups 3 and 5, respectively. The conception rate in groups 1, 2, 3, 4 and 5 were 33.33%, 50.00%, 75.00%, 83.33% and 0.00%, respectively. The mean serum progesterone in different groups increased non-significantly from days 0 to 21 post- insemination. All groups’ mean serum calcium increased significantly from day 0 to day 21. However, the mean serum phosphorus showed no such significant differences between and within the groups. It was noticed that the overall Ca:P ratio was disturbed (Ca being on the lower side) in the animals under study, which might be attributed to the animals’ anestrus condition. In conclusion, the Ovsynch, TRIU-B, and standard mineral mixture proved useful for induction of estrus and ovulation and enhancement of pregnancy rate in post-partum anestrus cows